The role of prematurity as a risk factor for stunting and its interaction with birth anthropometry in infants and toddlers - Syariena Syariena; Irma Ika Sari; Arindiah Puspo Windari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Stunting remains a major public health issue, particularly in developing countries, and is strongly influenced by conditions during pregnancy and early life. Prematurity and birth anthropometry, such as low birth weight and short birth length, are believed to be key determinants that increase the risk of growth failure in infants and toddlers. Purpose: to analyze the role of prematurity as a risk factor for stunting and examine its interaction with birth anthropometry among infants and toddlers. Method: This analytic observational study employed a case–control design involving 78 children aged 24–59 months, consisting of 39 stunted and 39 non-stunted children selected through total sampling. Data on birth history and nutritional status were collected, and stunting was determined using height-for-age z-scores (HAZ). Data analysis included chi-square tests for bivariate associations and logistic regression for multivariate analysis and interaction testing. Results: Among all respondents, 28.2% were born prematurely and 24.4% had low birth weight. Prematurity showed a significant relationship with stunting (p = 0.002), with premature children having a 3.12-fold higher risk of stunting. Multivariate analysis confirmed prematurity as a significant predictor (OR = 4.71; p = 0.004), while low birth weight also contributed significantly (OR = 2.97; p = 0.018). The interaction between prematurity and low birth weight demonstrated the strongest effect (OR = 5.48; p = 0.010), indicating that children with both risk factors have the highest likelihood of stunting. Conclusion: Prematurity and low birth weight are significant risk factors for stunting, and their interaction substantially increases the risk of growth failure. Strengthening maternal care, preventing premature births, and optimizing neonatal management for at-risk infants are essential strategies to reduce stunting prevalence.